Clinical significance of atypical glandular cells in Pap tests: An analysis of more than 3000 cases at a large academic women's center. Issue 8 (26th April 2016) - Pradhan, Dinesh; Li, Zaibo; Ocque, Rebecca; Patadji, Stell; Zhao, Chengquan
Abstract : BACKGROUND: The interpretation of atypical glandular cells (AGC) in Papanicolaou (Pap) tests and screening for glandular neoplasia remain challenging. METHODS: Pap tests with an AGC interpretation from January 2008 to December 2013 were retrieved from a pathology database, and cases with histologic follow‐up within 1 year were included in the study. RESULTS: There were 589, 830 Pap tests during the study period, and 3709 cases (0.6%) were reported as AGC, which included the following: AGC, not otherwise specified (52.0%); atypical endocervical cells (28.0%); and other categories. There were 3007 cases (81.1%) with histologic follow‐up results within 1 year. Cervical intraepithelial neoplasia 2/3 (CIN2/3), cervical adenocarcinoma in situ (AIS)/adenocarcinoma, and endometrial carcinoma were identified in 5.6%, 1.9%, and 5.5% of cases, respectively. Glandular neoplasia was more likely to be identified in cases with pure AGC subcategories than cases with AGC and squamous abnormalities. Endometrial neoplasia was more likely to be identified in cases with atypical endometrial cells than other categories. Overall, the most common severe abnormality on histologic follow‐up was CIN2/3. Although CIN2/3 was the most common severe lesion in patients younger than 30 years (10.0%) and in patients aged 30 to 49 years (6.4%), endometrial carcinoma was the most common lesion in women who were 50 years old or older (13.7%). Endocervical glandular lesions (AIS and adenocarcinoma) occurred in only 1.9% of women. CONCLUSIONS: AGC subtypes and ages significantly affect histological follow‐up results; 90.5% of cases with carcinoma on histologic follow‐up were either endometrial or metastatic carcinoma. This study supports the recommendation that women with AGC Pap test results should be followed up with both endocervical and endometrial sampling. Cancer Cytopathol 2016;124:589‐95 . © 2016 American Cancer Society . Abstract : Some patients with Papanicolaou tests showing atypical glandular cells (14.4%) have precancerous or malignant lesions on histologic follow‐up. Atypical glandular cell subtypes and ages significantly affect histological follow‐up results.